1, 25‐Dihydroxyvitamin D exerts an antiaging role by activation of Nrf2‐antioxidant signaling and inactivation of p16/p53‐senescence signaling. Issue 3 (24th March 2019) - Chen, Lulu; Yang, Renlei; Qiao, Wanxin; Zhang, Wei; Chen, Jie; Mao, Li; Goltzman, David; Miao, Dengshun
Abstract: We tested the hypothesis that 1, 25‐dihydroxyvitamin D3 [1α, 25(OH)2 D3 ] has antiaging effects via upregulating nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2), reducing reactive oxygen species (ROS), decreasing DNA damage, reducing p16/Rb and p53/p21 signaling, increasing cell proliferation, and reducing cellular senescence and the senescence‐associated secretory phenotype (SASP). We demonstrated that 1, 25(OH)2 D3 ‐deficient [1α(OH)ase −/− ] mice survived on average for only 3 months. Increased tissue oxidative stress and DNA damage, downregulated Bmi1 and upregulated p16, p53 and p21 expression levels, reduced cell proliferation, and induced cell senescence and the senescence‐associated secretory phenotype (SASP) were observed. Supplementation of 1α(OH)ase −/− mice with dietary calcium and phosphate, which normalized serum calcium and phosphorus, prolonged their average lifespan to more than 8 months with reduced oxidative stress and cellular senescence and SASP. However, supplementation with exogenous 1, 25(OH)2 D3 or with combined calcium/phosphate and the antioxidant N ‐acetyl‐l ‐cysteine prolonged their average lifespan to more than 16 months and nearly 14 months, respectively, largely rescuing the aging phenotypes. We demonstrated that 1, 25(OH)2 D3 exerted an antioxidant role by transcriptional regulation of Nrf2 via the vitamin D receptor (VDR). Homozygous ablation of p16 or heterozygous ablation of p53 prolonged the average lifespan of 1α(OH)ase −/− mice on the normal diet from 3 to 6 months by enhancing cell proliferative ability and reducing cell senescence or apoptosis. This study suggests that 1, 25(OH)2 D3 plays a role in delaying aging by upregulating Nrf2, inhibiting oxidative stress and DNA damage，inactivating p53‐p21 and p16‐Rb signaling pathways, and inhibiting cell senescence and SASP. Abstract : 1, 25(OH)2 D3 deficiency results in increasing oxidative stress through inhibiting transcription of Nrf2 and enhancing DNA damage; in addition, activation of p16/Rb and p53/p21 signaling occurs. These events then lead to inhibition of cellular proliferation and induction of cellular senescence and SASP, and thus acceleration of aging. These processes may be rescued to different degrees and aging postponed by supplementation of exogenous 1, 25(OH)2 D3, calcium/phosphate alone or combined calcium/phosphate and antioxidant NAC, or knockdown of p53 or knockout of p16.